2010
DOI: 10.1007/s00354-008-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Computing: a Perspective Study

Abstract: The Cloud computing emerges as a new computing paradigm which aims to provide reliable, customized and QoS guaranteed dynamic computing environments for end-users. In this paper, we study the Cloud computing paradigm from various aspects, such as definitions, distinct features, and enabling technologies. This paper brings an introductional review on the Cloud computing and provide the state-of-the-art of Cloud computing technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
272
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 617 publications
(285 citation statements)
references
References 5 publications
1
272
0
12
Order By: Relevance
“…According to Wang and von Laszewski [21], Cloud computing can be defined as "A computing Cloud is a set of network enabled services, providing scalable, QoS guaranteed, normally personalized, inexpensive computing platforms on demand, which could be accessed in a simple and pervasive way". Cloud computing has many differences to Grid computing technology.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wang and von Laszewski [21], Cloud computing can be defined as "A computing Cloud is a set of network enabled services, providing scalable, QoS guaranteed, normally personalized, inexpensive computing platforms on demand, which could be accessed in a simple and pervasive way". Cloud computing has many differences to Grid computing technology.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Computing Clouds operate like a central compute server with single access point. Cloud infrastructures could span several computing centers, which contain homogeneous resources operated under central control [21]. The next step of eScience will accommodate using Cloud infrastructure.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A lot of studies were developed to define cloud computing; we found it better to introduce them from two perspectives, the research groups' perspective and cloud professional users one. The NIST 1 , as a research institute, has defined the cloud computing as follows "Cloud computing is a model for enabling convenient, on-demand network access to a shared pool of configurable computing resources (e.g., networks, servers, storage, applications, and services) that can be rapidly provisioned and released with minimal management effort or service provider interaction." [9].…”
Section: Cloud Definitionmentioning
confidence: 99%
“…With the introduction to the new concept (software as a service) people started to learn and interact with the cloud in many fields [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, there have been a lot of successful attempts of incorporating Grid [23][24] [32] and Cloud technologies [1][2] [3] [18] [22] [25][27] to foster large simulations over the Internet, such as the Grid-aware Time Warp Kernel [16] and the HLA_Grid_RePast framework [5] [6]. However, these simulation systems are only suited for executing coarse-grained models due to the limited network bandwidth between different administrative domains.…”
mentioning
confidence: 99%